Adolescents' satisfaction with care for abortion‐related complications in 11 Sub‐Saharan African countries: A cross‐sectional facility‐based study. (22nd October 2021) - Eboigbe, Edua; Gadama, Luis; Filippi, Veronique; Mehrtash, Hedieh; Adu‐Bonsaffoh, Kwame; Bello, Folasade Adenike; Compaoré, Rachidatou; Dossou, Jean‐Paul; Idi, Nafiou; Kim, Caron R.; Msusa, Ausbert Thoko; Mugerwa, Kidza Yvonne; et al.
Abstract: Objective: To assess satisfaction with care for abortion‐related complications experienced among adolescents compared to older women. Methods: A secondary analysis of the WHO Multi‐Country Survey on Abortion‐related Morbidity and Mortality—a cross‐sectional study conducted in health facilities in 11 Sub‐Saharan African countries. Women with abortion‐related complications who participated in an audio computer‐assisted self‐interview were included. Two composite measures of overall satisfaction were created based on five questions: (1) study participants who were either satisfied or very satisfied across all five questions; and (2) study participants who reported being very satisfied only across all five questions. Multivariable general estimating equation analyses were conducted to assess whether there was any evidence that age (adolescents 12–19 years and older women 20+) was associated with each composite measure of satisfaction, controlling for key confounders. Results: The study sample consisted of 2817 women (15% adolescents). Over 75% of participants reported being satisfied or very satisfied for four out of five questions. Overall, 52.9% of study participants reported being satisfied/very satisfied across all five questions and 22.4% reported being consistently very satisfied. Multivariable analyses showed no evidence of an association between age group and being either satisfied or very satisfied (OR 1.07; 95% CI, 0.82–1.41, P  = 0.60), but showed strong evidence that adolescents were 50% more likely to be consistently very satisfied with their overall care than older women (OR 1.49; 95% CI, 1.13–1.96, P  = 0.005). Conclusion: Both adolescents and older women reported high levels of satisfaction with care when looking at different components of care individually, but the results of the composite measure for satisfaction showed that many study participants reported being less than satisfied with at least one element of their care. Further studies to explore the expectations, needs, and values of women's satisfaction with care for abortion‐related complications are needed. Synopsis: This study found that patient satisfaction with care for abortion‐related complications was similar among adolescents and older women across 11 Sub‐Saharan African countries.